KAJIAN BUDAYA ORGANISASI, KEPEMIMPINAN STRATEJIK, HUMAN CAPITAL DAN KINERJA BADAN USAHA MILIK DAERAH (BUMD) DI PROVINSI RIAU - Mampanini, Dianto (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This research aims to develop a conceptual study of Organizational Culture, Strategic Leadership, Human Capital and BUMD Performance in Riau Province. This research uses a qualitative approach and research data collection techniques using interviews. The findings in this research are: 1) Performance is still relatively low, this can be seen from the realization of targets where there are still many BUMDs that have not been able to achieve targets; 2) Organizational culture cannot be implemented by all directors, this is because there are still several BUMDs that do not have core values; 3) Strategic leadership has been implemented by the board of directors, where the board of directors has tried as optimally as possible to implement the vision and mission, make strategic plans, adapt to changes in technology and the environment, make decisions by involving stakeholders, have good emotional intelligence and moral intelligence; 4) Human capital is still relatively poor, as can be seen from the fact that there are still directors whose experience does not match the company's type of business. Meanwhile, if you look at the competency and training that the board of directors already have, there are still obstacles in implementing knowledge management; 5) Performance improvement strategy, namely by paying attention to strengths, weaknesses, opportunities and threats; 6) BUMD directors and shareholders must work together to create policies that continue to pay attention to the company's progress and goals; 7) BPSDM Riau Province, can play a role in improving the performance of BUMD, by providing training in technical competence, managerial competence and sociocultural competence; 8) To build organizational culture, develop strategic leadership and human capital, BPSDM must provide training that focuses on technical competence, managerial competence and sociocultural competence.